HUBUNGAN USIA DAN JARAK KEHAMILAN DENGAN KEJADIAN ABORTUS - Nuri Luthfiatil Fitri (AKPER Dharma Wacana, 2017)
Abortion as one of the causes of maternal death is a matter of great concern. According to the WHO estimated at 15% -50% of maternal deaths associated with abortion. In Southeast Asia the annual incidence of abortion reaches 4.2 million and in Indonesia it reaches 1.5 million. The purpose of this study is to know the correlations between age and gestational distance with the incidence of abortion in hospitals Jend. Ahmad Yani Metro in 2015. The type of analytic survey research using case control approach. The population in this study were all pregnant women who were treated in RSUD Jend. Ahmad Yani Metro in 2014, amounting to 518 people with samples taken as many as 260 people consisting of 130 people in the case group and 130 people for the control group. The analysis in this study used chi square test. The results of statistical tests showed that there was an association of age with abortus occurrence (p-value 0,000 OR 4.021; CI; 95%: 2,161-7,483), there was a correlation between pregnancy distance and abortus occurrence (p-value: 0,000, OR 3.955; CI; 95 %: 2,354-8,556). Research shows there is a correlations between age and gestational distance with the incidence of abortion.